Responder
Here are the simplified answers to the fraction problems:
1. **Problem 3:** \(\frac{11}{6}\) or \(1 \frac{5}{6}\)
2. **Problem 4:** \(-\frac{4}{3}\)
3. **Problem 5:** \(-\frac{7}{9}\)
4. **Problem 6:** \(\frac{11}{24}\)
5. **Problem 7:** \(-\frac{8}{9}\)
6. **Problem 8:** \(\frac{143}{60}\) or \(2 \frac{23}{60}\)
Solución
Sure! Let's solve each of the given fraction problems step by step.
---
### **Problem 3**
\[ \frac{1}{3} + \frac{5}{6} \div \frac{5}{9} \]
**Step 1: Perform the Division**
\[
\frac{5}{6} \div \frac{5}{9} = \frac{5}{6} \times \frac{9}{5} = \frac{45}{30} = \frac{3}{2}
\]
**Step 2: Add the Result to \(\frac{1}{3}\)**
\[
\frac{1}{3} + \frac{3}{2} = \frac{2}{6} + \frac{9}{6} = \frac{11}{6} \text{ or } 1 \frac{5}{6}
\]
**Answer:** \(\frac{11}{6}\) or \(1 \frac{5}{6}\)
---
### **Problem 4**
\[ -\frac{8}{9} + \frac{1}{9} \div \left(-\frac{1}{4}\right) \]
**Step 1: Perform the Division**
\[
\frac{1}{9} \div \left(-\frac{1}{4}\right) = \frac{1}{9} \times (-4) = -\frac{4}{9}
\]
**Step 2: Add the Results**
\[
-\frac{8}{9} + \left(-\frac{4}{9}\right) = -\frac{12}{9} = -\frac{4}{3}
\]
**Answer:** \(-\frac{4}{3}\)
---
### **Problem 5**
\[ \frac{7}{8} \times \left(-\frac{7}{9} - \frac{1}{9}\right) \]
**Step 1: Simplify Inside the Parentheses**
\[
-\frac{7}{9} - \frac{1}{9} = -\frac{8}{9}
\]
**Step 2: Multiply**
\[
\frac{7}{8} \times \left(-\frac{8}{9}\right) = -\frac{56}{72} = -\frac{7}{9}
\]
**Answer:** \(-\frac{7}{9}\)
---
### **Problem 6**
\[ \frac{1}{3} \times \left(\frac{5}{8} + \frac{3}{4}\right) \]
**Step 1: Simplify Inside the Parentheses**
Convert \(\frac{3}{4}\) to eighths:
\[
\frac{3}{4} = \frac{6}{8}
\]
Add the fractions:
\[
\frac{5}{8} + \frac{6}{8} = \frac{11}{8}
\]
**Step 2: Multiply**
\[
\frac{1}{3} \times \frac{11}{8} = \frac{11}{24}
\]
**Answer:** \(\frac{11}{24}\)
---
### **Problem 7**
\[ \frac{4}{9} - \frac{2}{9} \div \frac{1}{3} + \left(-\frac{2}{3}\right) \]
**Step 1: Perform the Division**
\[
\frac{2}{9} \div \frac{1}{3} = \frac{2}{9} \times 3 = \frac{6}{9} = \frac{2}{3}
\]
**Step 2: Substitute Back Into the Expression**
\[
\frac{4}{9} - \frac{2}{3} + \left(-\frac{2}{3}\right)
\]
Convert all fractions to ninths:
\[
\frac{4}{9} - \frac{6}{9} - \frac{6}{9} = \frac{4 - 6 - 6}{9} = \frac{-8}{9}
\]
**Answer:** \(-\frac{8}{9}\)
---
### **Problem 8**
\[ \frac{3}{5} + \frac{7}{15} \div \frac{4}{5} - \left(-1 \frac{1}{5}\right) \]
**Step 1: Perform the Division**
\[
\frac{7}{15} \div \frac{4}{5} = \frac{7}{15} \times \frac{5}{4} = \frac{35}{60} = \frac{7}{12}
\]
**Step 2: Simplify the Negative Term**
\[
-\left(-1 \frac{1}{5}\right) = +1 \frac{1}{5} = \frac{6}{5}
\]
**Step 3: Combine All Terms**
\[
\frac{3}{5} + \frac{7}{12} + \frac{6}{5}
\]
Find a common denominator (60):
\[
\frac{3}{5} = \frac{36}{60}, \quad \frac{7}{12} = \frac{35}{60}, \quad \frac{6}{5} = \frac{72}{60}
\]
Add them together:
\[
\frac{36}{60} + \frac{35}{60} + \frac{72}{60} = \frac{143}{60} = 2 \frac{23}{60}
\]
**Answer:** \(\frac{143}{60}\) or \(2 \frac{23}{60}\)
---
If you have any more problems or need further clarification, feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución